Keterampilan Pertolongan Pertama pada Fraktur di SMA Negeri 1 Gowa - Andi Budiyanto Adi Putra; Fitrawati Arifuddin; Bayu Nur Mahis; Ansyaruddin Samad (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Fracture is one of the emergency conditions that frequently occurs in the school environment, particularly during physical and sports activities. Inappropriate initial management can lead to various complications; therefore, first aid skills among students, especially members of the School Health Unit (Unit Kesehatan Sekolah/UKS), are essential. This study aimed to describe first aid skills in fracture cases among UKS students at SMA Negeri 1 Gowa before and after skills evaluation. This study employed a quantitative descriptive design with a cross-sectional approach. The population consisted of all UKS members at SMA Negeri 1 Gowa, totaling 34 students, and the entire population was included as the sample using a quota sampling technique. Data were collected using an observation checklist to assess first aid skills for fracture management. Data analysis was conducted descriptively by presenting frequency distributions and percentages. The results showed that during the pre-test, most respondents were categorized as having poor first aid skills, with 18 students (52.9%), while 16 students (47.1%) were categorized as having good skills. In the post-test, an improvement in first aid skills was observed, as the number of respondents with good skills increased to 24 students (70.6%), while those with poor skills decreased to 10 students (29.4%). In conclusion, this study demonstrated an improvement in first aid skills for fracture management among UKS students at SMA Negeri 1 Gowa after the skills evaluation. Therefore, it is recommended that continuous training and guidance on fracture first aid be implemented to enhance students’ preparedness in handling emergency situations within the school environment.